THE USE OF MATHEMATICAL METHODS IN THE STUDY OF THE PROCESS OF THERMAL EROSION - Baranova N.A. (My University, 1996)
The occurrence and development of thermal erosion are affected by many factors: climate, geomorphology, geology and geocryology. The paper presents a mathematical model which can be used to calculate the parameters of thermal erosion involving planar erosion and the eroding effect of small temporary streams of meltwater, leading to the formation of thermo-erosional ditches, gullies and other erosional relief forms. The calculations were tested using data about the Anabar area and used to construct a map of regions at risk from thermal erosion.